PENGARUH PROGRESSIVE MUSCLE RELAXATION PADA KEHAMILAN: A LITERATURE REVIEW - Rizqi Dian Pratiwi; Raffiky Pinandia Sustamy (Journal of Midwifery and Health Administration Research, 2021)
Background: The discomfort felt during pregnancy can make the mother anxious and will effected health problems for the mother and fetus. But efforts efforts to solve them by paying attention to physical and psychological aspects are not optimal. The aims of this study is to know the effect of Progressive Muscle Relaxation (PMR) therapy for discomfort during pregnancy. Methods: The method used is a literature review by searching electronic database Science Direct, Pubmed and Google Scholar. Progressive Muscle Relaxation and pregnancy were used as keywords in searching strategy. A total of 9 from 29.714 of publication range from 2010 - 2021 and presented in English language and use Randomized Controlled Trials (RCTs) that are relevant to the PMR technique were include in this review. Results Studies show that many of the effects of PMR during pregnancy effectively reduce complaints of physical symptoms, reduce anxiety, improve sleep quality, improve quality of life, reduce low back pain, reduce hyperemesis gravidarum, prolonged pregnancy in preterm labor, control blood sugar and blood pressure and have a positive influence on the fetus and after birth. Conclusions: Overall, studies that have been reviewed indicate that PMR is effectively giving more benefits and no adverse effects are reported.